As infecções sexualmente transmissíveis e a promoção da saúde sexual em uma escola rural de ensino médio. - Maurìcia Paula da Silva Santos (2024)
This work aimed at promote sexual health education by addressing aspects related to STIs with an emphasis on the Human Papillomavirus (HPV) in a rural school. The methodology used was based on the application of Didactic Sequence (DS) for 3rd year high school students by means of the creation of hypotheses about the causes, effects and consequences of HPV and discussion between peers, presentation of data obtained via documentary research on the problem situation, preparation of promotional material and STI prevention campaign, application of a board game about HPV. The strategies presented were created to compare previous knowledge and that acquiredone by the participation in this study. Questionnaires were administered before and after completing the SD. It was possible verifying by means of the qualitative analysis of the data, that the students acquired knowledge about STIs and HPV after completing the DS, which can be considered as an advance in relation to the level of knowledge on the subject. Therefore, given the importance of constructing knowledge by means of an effective and meaningful teaching-learning process, it is understood that the application of the SD with the game tool was efficient and complemented teaching through investigation